2007
DOI: 10.1007/978-3-540-73354-6_102
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Illumination Control Method to Improve Office Productivity

Abstract: Abstract.A lighting control method has been proposed which adjusts the circadian rhythms of office workers and eliminates a decrease in the arousal level in the afternoon by exposing a high intensity of light in the morning in order to improve their productivity. As a result, it was found that the task performance of the CPTOP test under 2,100 lx was significantly higher than that under 700 lx and more than a 9% improvement of task performance was achieved. Furthermore, a demonstration experiment has been cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Researches regarding illuminance and color temperature have already been carried out, and it has been reported that when illuminance is increased an office worker's level of alertness can be maintained at a high level and work efficiency can be increased [3]. Additionally, it was also found that a low level of color temperature creates a feeling of relaxation with redtinted colors, and conversely creates a feeling of refreshment at high color temperature with pale, bluish colors [11].…”
Section: A Effects Of Illuminance and Color Temperature On Peoplementioning
confidence: 93%
See 2 more Smart Citations
“…Researches regarding illuminance and color temperature have already been carried out, and it has been reported that when illuminance is increased an office worker's level of alertness can be maintained at a high level and work efficiency can be increased [3]. Additionally, it was also found that a low level of color temperature creates a feeling of relaxation with redtinted colors, and conversely creates a feeling of refreshment at high color temperature with pale, bluish colors [11].…”
Section: A Effects Of Illuminance and Color Temperature On Peoplementioning
confidence: 93%
“…And it has been clarified that to provide illuminance most suitable for execution of work for each individual is effective from the viewpoint of improving the lighting environment [2]. Particularly, It has been reported that providing proper illuminance is effective for improving the light environment and increasing intellectual productivity and work efficiency in office spaces [3]. It is also clear that the preferred lighting environment differs depending on biological rhythms, work content, individuals and their health condition [4] [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the pre-pandemic period, people spent a significant amount of time in a working day, approximately 8 h, in their offices [25] or outside their residential buildings. With the new dynamics that COVID-19 brought to people's lives, daily routines were forced to be practiced in the living areas.…”
Section: Activity In Living Areamentioning
confidence: 99%
“…2 Masanori Tsujikawa is with Biometrics Research Laboratories, NEC Corporation, Japan. 3 Atsushi Nishino and Satoshi Hashimoto are with Technology and Innovation Center, Daikin Industries, LTD, Japan.…”
Section: Introductionmentioning
confidence: 99%